2021
DOI: 10.1016/j.ygyno.2021.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial ovarian cancer and the use of circulating tumor DNA: A systematic review

Abstract: Circulating tumor DNA as a biomarker in epithelial ovarian cancer is promising in several settings.• The methods used to analyze circulating tumor DNA in epithelial ovarian cancer need to be optimized.• Further studies are needed to establish the use of circulating tumor DNA in the clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…Liquid biopsy has many clinical impacts. Recent studies have shown that detected positive cases have poorer survival than detected negative cases including therapeutic response and prognosis [44][45][46][47][48]. This is consistent with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…Liquid biopsy has many clinical impacts. Recent studies have shown that detected positive cases have poorer survival than detected negative cases including therapeutic response and prognosis [44][45][46][47][48]. This is consistent with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…ctDNA has better diagnostic performance compared to traditional CA-125 with several studies demonstrating that quantitative analysis of ctDNA has a relatively high specificity of 88% and sensitivity ranging from 27–100% [ 92 , 162 168 ]. A recent systematic review of 23 studies evaluating ctDNA for the diagnosis of EOC in symptomatic patients preoperatively yielded similar results [ 89 , 96 , 153 , 154 , 156 158 , 160 162 , 166 , 167 , 169 179 ]. Other studies that evaluated ctDNA analysis in HGSOC patients for TP53 mutation detection, reported high sensitivity (75–100%) and specificity (> 80%) [ 45 , 89 91 ].…”
Section: Clinical Applications Of Liquid Biopsy For Ovarian Cancermentioning
confidence: 78%
“…Recently, advances in therapeutic monitoring in EOC have been made with circulating tumor DNA (ctDNA) providing important evidence about its utility in determining outcome and individualizing cancer therapy in patients with EOC [65][66][67]; on the contrary, the role of circulating miRNAs in EOC clinical monitoring needs to be further investigated in order to obtain a larger concordance between the results from independent investigators. Of note, we should bear in mind that ctDNA represents a sort of barcode originating directly from the tumor, but "liquid" miRNAs are not derived uniquely from the cancerous mass.…”
Section: Discussionmentioning
confidence: 99%